GEOCHEMICAL- MINERALOGICAL AND METALLOGENETICAL ASPECTS CONCERNING THE ORIGIN OF SEDIMENTS FROM LEG. 22 D.S.D.P DRILLED SITES 212 AND 213 IN EASTERN INDIAN OCEAN - Papavassiliou, C. T. (Bulletin of the Geological Society of Greece, 2007)
Basic mineralogical and geochemical data, are presented for sediment core samples from Deep Sea Drilling Project(D.S.D.P) boreholes .Sites 212 and 213 respectively, from the eastern Indian Ocean. In both Sites the Fe-Mn oxides are abundant controlling a numerous suite of trace elements. In Site 212 the Fe-Mn oxides are more abundant in the upper part of the borehole having mainly a diagenetic or hydrogenous origin, whilst in Site 213 these oxides are more abundant in the lower part having mainly a hydrothermal origin. In both Sites clay minerals are consisting mostly of the expandable mixed layered smectite/illite. The geochemical data shows that in both Sites the majority of the sediments have the characteristics of typical deep sea clay being both of detrital and authigenic origin. In Site 212 these clays with considerable amount of palygorskite and the zeolite clinoptilolite, both of authigenic origin, opaline silica, biogenous CaCOj ,the Fe-Mn oxides and some other detrital minerals together control the bulk chemical composition of the sediments. In Site 213 the clays with large amounts of Fe-Mn oxides and considerable amounts of the zeolite Phillipsite and Palygorskite in small amounts and some other detrital minerals, control the chemical composition of the sediments. The increase in the Ti/Al and Mg/Al ratios with depth in both Sites implies a volcanoclastic input in the bottom sediments probably from the underlying basaltic basement